Experiencing the Essence of Catholic Marriage in the Hubula Catholic Family at the Emanuel Parish in Elagaima - Elopere, Abmita Michalia; Tan, Paulus Satyo Istandar (Kariwari: Jurnal Pendidikan Agama Katolik dan Pastoral, 2025)
This study aims to determine the extent to which Hubula Catholic families in Emanuel Elagaima Parish understand and internalize the essence of Catholic marriage and to identify supporting and inhibiting factors. This study used a qualitative approach using in-depth interviews, focus group discussions, and observation. The results indicate that Hubula Catholic families understand marriage as a sacred bond originating from God, which demands fidelity, love, openness to life, and mutual affection. However, despite efforts to faithfully live out Catholic marriage, some still face difficulties, such as marrying according to traditional customs without the sacrament or practicing polygamy. Supporting factors for the internalization of Catholic marriage include involvement in the sacrament, pastoral support from the Church, and the couple's commitment to faithfulness. Inhibiting factors include traditional pressure, a lack of understanding of the faith, and minimal ongoing pastoral care. This study emphasizes the need for an active role for the Church in providing guidance and faith education for Hubula Catholic families to harmonize Catholic teachings with local culture so that marriage is truly experienced as a divine calling that unites couples in the love of Christ.